Analysis on the Land Transition in Gunungkidul using Multi Temporal Remote Sensing - Wahyu Wardhana; Junun Sartohadi; Lies Rahayu; Andri Kurniawan (Jurnal Ilmu Kehutanan)
Gunungkidul was well known as barren area during 1940-1970 but now becomes fully vegetated. This process called the transition process. This study provided empirical evidences by spatial changes and remote sensing analysis and then the results were used for modelling of  the transition phases according to Mather (1992) and Hosunuma (2002). According to the model, the current transition phase is close to the final stage of the growth process. A unique phenomenon of the transition process of re-vegetation is that the regions dominated by settlement/yard, rain fed and upland/fields (in accordance to SNI 7645-2010). This model could be categorize as model of new ecosystem in the transition process, which is different from the previous one. The previous model was in the form of mixed forest as described by Nibbering(1991). This model is a compromise form of socio-ecological aspect as a result of the rehabilitation process, which was conducted by either the public or the Local Government based on Greening  Program of the Central Government according to Presidential Instruction. Interested learning from the process of re-vegetation transition is that the formations of re-vegetation lead to a new ecosystem in Gunungkidul through the dominance of settlement, rain field and upland.